Proyecto de Factibilidad para la implementación de una Empresa Productora y Comercializadora de una bebida energizante natural a base de la fruta de borojo en la Ciudad de Loja - Mora García, Jorge Luis (2016)
This research has as purpose the development of a "project of factibility for the implementation of a company producer and marketer of a drink ENERGIZING NATURAL based LA fruit of BOROJO in the city of LOJA" was performed in order to check the feasibility of the project to startup company, for which the use of methods took into account analytical inductive, deductive, descriptive, scientific, historical and synthetic and techniques such as survey and sampling that allowed me to segment the population so that the product is aimed for the economically active population by reducing the percentage of people with some form of heart disease. This research begins with the Study Market where it was determined that the target market for this product is the economically active population, and by analyzing the demand and supply unmet demand for the first year of 1'994.543 liters identified energizing bottles that is an amount of 6,593,486.27. Then a Technical Study identified that the ability to be used by the company is 166,400 liters per year generating a production of 545,574 bottles of 305 ml Energizing performed. a year, the most suitable location for the plant is in the Industrial Park located in Salvador Bustamante Celi Streets and Av. December 8, the company will be incorporated as a Limited Company, formed by three partners. In the Financial Study it was determined that this business requires an initial investment of $ 189.205,16 the same as the 60% financed by contributions from partners and 40% for bank loan. 5 Through Budget Proformado a total cost of production for the year one is $379.049,38 which gives a unit cost of $ 0.69 Production which adding a profit margin of 42% was obtained, obtaining a Asking Price unit of $ 1.00 multiplied by 545,574 units produced not give an income of $538.250,12. By developing the Profit and Loss evidence for the first year of operations is useful Liquid $ 94.995,98 Financial evaluation was carried out starting with the construction of Cash Flow in the first year gives a flow of $ 134.986,54, then financial indicators such as net present value which is $ 376.301,05 which was analyzed shows that the project is feasible since NPV exceeds the value of the investment, internal rate of return is 69.59% which shows that the company is able to pay up to 69,59% interest to a financial institution, the indicator Relations cost Benefit shows me that for every dollar invested company earns 44 cents., the Recovery Period Capital shows that the investment is recovered in 1 years, 4 months and 20 days, the sensitivity analysis shows that the product isn`t sensitive to increase 19% in costs and the decrease of 13.50% in revenue. According to the above it is determined that the project is feasible and profitable.